Do non-citizens migrate for welfare benefits? Evidence from the Affordable Care Act Medicaid expansion - Hao Guo; Miaomiao Zou (Frontiers in Public Health, 2022)
We explore if low-educated noncitizens, who have a considerably high uninsured rate, internally migrate to states with more generous public insurance benefits. We utilize the state-level variation in accessing Medicaid benefits and employ a difference-in-differences methodology that compares in-migration and out-migration rates of non-citizens in states that adopted Medicaid expansion, both before and after the policy implementation, to the outcomes of non-citizens in states that did not adopt the expansion. We find that interstate in-migration (out-migration) rates of Medicaid expansion states did not increase (decrease) relative to that of non-expansion states after the expansion.